Effects of viscous dissipative MHD fluid flow past a moving vertical plate with rotating system embedded in porous medium - Santhi Kumari, Dharani Kota; Sajja, Venkata Subrahmanyam; Kishore, Perugu Mohana (Zielona Góra: Uniwersytet Zielonogórski)
An incompressible unsteady free convective viscous MHD rotating flow past a moving plate embedded in a porous medium is considered with the influence of viscous dissipation, heat source effects. It is assumed that the flow rotates with angular velocity which is normal to the plate and also that a transverse magnetic field is applied along the normal to the plate.
Keywords: rotation; chemical reaction; heat source; viscous dissipation; porous medium